2006
DOI: 10.1074/jbc.m606500200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Substrate Specificity of PhlD, a Type III Polyketide Synthase fromPseudomonas fluorescens

Abstract: PhlD, a type III polyketide synthase from Pseudomonas fluorescens, catalyzes the synthesis of phloroglucinol from three molecules of malonyl-CoA. Kinetic analysis by direct measurement of the appearance of the CoASH product (k cat ‫؍‬ 24 ؎ 4 min ؊1 and K m ‫؍‬ 13 ؎ 1 M) gave a k cat value more than an order of magnitude higher than that of any other known type III polyketide synthase. PhlD exhibits broad substrate specificity, accepting C 4 -C 12 aliphatic acyl-CoAs and phenylacetyl-CoA as the starters to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…This tunnel assists the binding of long chain acyl-CoAs by means of dynamically increasing the volume of the active site cavity. The saturation mutagenesis on the tunnel successfully altered the substrate specificity of PhlD, which demonstrated that even subtle changes in the tunnel volume could affect the ability of PhlD to accept long chain acyl-CoAs and explained the high reactivity of PhlD with various substrates (30).…”
Section: Bacterial Type III Pkssmentioning
confidence: 99%
See 1 more Smart Citation
“…This tunnel assists the binding of long chain acyl-CoAs by means of dynamically increasing the volume of the active site cavity. The saturation mutagenesis on the tunnel successfully altered the substrate specificity of PhlD, which demonstrated that even subtle changes in the tunnel volume could affect the ability of PhlD to accept long chain acyl-CoAs and explained the high reactivity of PhlD with various substrates (30).…”
Section: Bacterial Type III Pkssmentioning
confidence: 99%
“…Finally, PKS18 from Mycobacterium tuberculosis has been shown to accept longchain aliphatic acid CoA-esters (C 6 -C 20 ) as the starter units to produce triketide or tetraketide pyrones via two or three condensation reactions (37). The crystal structure of PKS18 reveals a 20 Å substrate binding tunnel that allows this synthase to utilize a broad range of substrates, similar to PhlD (30). In addition to PKS18, several bacterial type III PKSs including PKS11 and SCO7671 from S. coelicolor were found to use long-chain fatty acid CoA-esters as the starter units (37).…”
Section: Bacterial Type III Pkssmentioning
confidence: 99%
“…Homology modeling of PfPhlD using the structure of THNS as a reference highlighted the presence of a similar buried tunnel extending into the 'floor' of the active site cavity, which can potentially aid the binding of long chain acyl-CoAs [68]. The different reactivity towards phenylacetyl-CoA might suggest a larger and more flexible tunnel in PfPhlD that is capable of incorporating the bulky starter, compared to RppA.…”
Section: Phloroglucinol Synthase From Pseudomonas Fluorescensmentioning
confidence: 99%
“…These structural studies have provided insights into the mechanistic details of type III PKSs, illustrating how subtle modifications in the active site cavity can expand the biosynthetic repertoire and result in the generation of diverse products. Manipulation of active site residues by random mutagenesis [68] and/or site-directed mutagenesis has proved useful in the understanding of and subsequently, engineering of the substrate specificity and activity of type III PKSs.…”
Section: Insights Into Mutagenesis Studiesmentioning
confidence: 99%
“…The locus contains four genes, phlA, phlC, phlB, and phlD, which are transcribed as a single operon (phlACBD) (13). The phlD gene encodes a type III polyketide synthase, which is responsible for the synthesis of phloroglucinol (PG) from three molecules of malonyl-coenzyme A (CoA) (17,18,19). The phlA, phlC, and phlB genes together are required for conversion of PG to monoacetylphloroglucinol (MAPG) and of MAPG to 2,4-DAPG (13,20).…”
mentioning
confidence: 99%